The Effect of Intracanal Medicament Using Calcium Hydroxide in Root Canal Infection Toward MMP-9, TIMP-1 and EGF Level in Apical Lesion: a Literature Review - Ni Kadek Eka Widiadnyani (Journal of Global Pharma Technology, 2020)
Root canal infection is one of periodontitis spectrum that started by dental caries process. There are many bacteria causing root canal infections, mainly obligate anaerobe bacteria. Root canal infection can form apical lesions resulted from the interaction between bacteria and inflammatory cells. The apical lesion can be causing degradation of the extracellular matrix in the root canal system. Collagen degradation is the main characteristic of the apical lesion, which degradation process mediated by pro-inflammatory cells. One of them is a matrix metalloproteinase (MMP) mainly MMP Type-9 (MMP-9). Besides MMP, tissue inhibitor of MMP (TIMP) and epidermal growth factor (EGF) also play a role as MMP regulators. Root canal treatment with intracanal medicament needed to fix dental tissue destruction. There are many intracanal medicaments available, which is calcium hydroxide mostly used in dental therapy. Calcium hydroxide has an antibacterial effect and can be lowering inflammatory cells number. In apical lesion, immune-inflammatory response happened which inflammatory cells play an important role in extracellular matrix degradation. Studies showed that intracanal medicament using calcium hydroxide proven lowering inflammatory cells levels such as MMP-9, TIMP-1 and EGF. This review will have further discussion about calcium hydroxide mechanism in reducing MMP-9, TIMP, and EGF levels in the apical lesion. Keywords: Root canal infection, Intracanal medicament, MMP-9, TIMP-1, EGF.